Anti-sintering platinum-based catalyst as well as preparation and application thereof

By loading PT on the structure of magnesium aluminum spinel, adjusting the MG/Al Moorbi and roasting conditions, preparing a anti -sintering platinum base catalyst, solving the problem of insufficient stability and activity at high temperature at high temperatures, realizing Efficient purification effect.

CN119368170AActive Publication Date: 2025-01-28EAST CHINA UNIV OF SCI & TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411929773.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-28
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing anti-sintered platinum catalysts have poor stability and poor activity under high temperature conditions, and are complex in synthesis and inconvenient in operation, making it difficult to meet industrial needs.

Method used

The magnesium aluminum spinel structure catalyst with load PT is adopted. By adjusting the MG/Al Moorbi and baking conditions, the presence of PT is controlled to ensure that the catalyst is oxidized or restored in the atmosphere of the catalyst at 800 ° C ~ 1000 ° C.

Benefits of technology

The high stability and activity of catalysts can be achieved, and good purification efficiency can be maintained at high temperature conditions, and it is suitable for response such as acrylic catalytic combustion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368170A_ABST
    Figure CN119368170A_ABST
Patent Text Reader

Abstract

The invention relates to an anti-sintering platinum-based catalyst and preparation and application thereof, the catalyst is a Pt-loaded magnesium aluminate spinel structure catalyst, and the total mass percentage of Pt in the catalyst is 0.1-4 wt%. The preparation method of the catalyst comprises the following steps: preparing a PtMgxAl2Oy solid solution; and finally, adjusting a roasting atmosphere to generate Pt particles on the surface of the PtMgxAl2Oy solid solution in situ. Compared with the prior art, by adjusting the feeding proportion of the Mg source and the Al source and controlling the number of the Mg sites lacking in the crystal lattice of the sharp crystal structure, it is ensured that the precious metal Pt can occupy the Mg sites in the spinel crystal lattice, meanwhile, the roasting atmosphere and temperature are adjusted, and the number of the precious metal Pt nano-particles can be adjusted and controlled; the obtained catalyst has high reaction activity and excellent anti-sintering capability for treating the common atmosphere pollution substance propylene. The preparation method has the advantages of simple and feasible synthesis steps, good reproducibility, easiness in control and adjustment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of catalytic technology and environmental catalysis, and in particular to a sintering-resistant platinum-based catalyst and a preparation method and application thereof. Background Art

[0002] The elimination of low-concentration pollutants often uses precious metal platinum catalysts. Although the mass fraction of platinum in these catalysts is low, it can show good pollutant elimination effects. However, in actual use, the platinum component may be sintered due to the high temperature (greater than or equal to 800 ℃) conditions. This sintering phenomenon will be more serious when the atmosphere contains reducing gases. Sintering often leads to a significant decrease in purification efficiency. It is difficult to regenerate the sintered catalyst to restore the original purification efficiency. Therefore, it is very practical and economically meaningful to design and develop platinum catalysts with excellent sintering resistance.

[0003] The existing patented technologies for synthesizing sinter-resistant platinum catalysts (CN104338530B, CN105964274A and CN108355649A) basically have the disadvantages of inconvenient operation and complex raw materials. Although there are examples of precious metal components that can withstand high temperatures of 900°C or higher in the above technologies, these technologies all have certain problems of poor stability and poor activity. For example, in CN104338530B, the gold-platinum-palladium alloy particles grow to 9.2 nm in size after being treated at 900°C, and in CN108355649A, when the precious metal catalyst treated at 950°C is used in the actual low-concentration propylene combustion elimination reaction, its ignition temperature is higher than 200°C, which does not meet the requirements of low temperature and high purification efficiency.

[0004] In summary, it is still difficult to simply synthesize high-activity platinum catalysts that are resistant to high-temperature sintering. Therefore, it is urgent to develop sintering-resistant Pt catalysts to meet actual industrial needs. Summary of the invention

[0005] The purpose of the present invention is to provide a sintering-resistant platinum-based catalyst and a preparation method thereof in order to overcome the defects of the above-mentioned prior art, and the catalyst has good stability and activity.

[0006] The purpose of the present invention can be achieved by the following technical solutions: One of the technical solutions of the present invention is to provide a sintering-resistant platinum-based catalyst, which is a magnesium-aluminum spinel structure catalyst loaded with Pt, the total mass percentage of Pt in the catalyst is 0.1~4 wt%, the size is 0.4-2.5 nm, and the magnesium-aluminum element ratio in the catalyst is 0.8~0.99:2.

[0007] Furthermore, the Pt component exists in the catalyst in two forms, one is in the form of metal nanoparticles on the surface of magnesium-aluminum spinel, and the other is in the form of high-valent cations located at the missing magnesium sites in the magnesium-aluminum spinel lattice.

[0008] Furthermore, the Pt component in the catalyst is resistant to sintering in an oxidizing atmosphere at 800°C to 1000°C or a reducing atmosphere at 800°C to 1000°C.

[0009] The second technical solution of the present invention is to provide a method for preparing a sintering-resistant platinum-based catalyst, comprising the following steps: (1) Dissolve the corresponding salts of Pt source precursor, Mg source and Al source precursor in deionized water, with the Mg / Al molar ratio being 0.8:2~0.99:2, and then add excess alkali to control the pH to 11~12; (2) allowing the resulting suspension to stand, filtering and washing the resulting precipitate, drying it, and grinding it into powder; (3) calcining the powdered solid at 800°C to 1000°C in air for 3 to 9 h to obtain a precursor in which platinum ions are located inside the crystal lattice; (4) The precursor obtained in step (3) is calcined at 800°C to 1000°C in a reducing atmosphere for 3 to 9 h to obtain the target catalyst PtMg x Al2O y .

[0010] Furthermore, in step (1), the Pt source precursor includes platinum acetylacetonate, chloroplatinic acid, platinum nitrate or tetraammineplatinum nitrate.

[0011] Furthermore, the Mg source and Al source precursors in step (1) include corresponding sulfates, halides, nitrates or acetates, and the base used includes NaOH, Na2CO3, KOH or K2CO3.

[0012] Furthermore, the air condition in step (3) includes static and flowing states.

[0013] Furthermore, the reducing atmosphere in step (4) includes CO or H2 or a mixture thereof.

[0014] Furthermore, by adjusting the feed ratio of Mg source and Al source, the number of missing Mg sites in the spinel structure lattice is controlled so that Pt is located at the missing magnesium sites. At the same time, by adjusting the calcination temperature and calcination atmosphere of step (3) and step (4), the number of surface Pt metal nanoparticles is adjusted. The higher the reduction temperature, the greater the number of exposed metal Pt nanoparticles.

[0015] The third technical solution of the present invention is to provide an application of a sintering-resistant platinum-based catalyst, and to use the catalyst for catalytic combustion of propylene.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention utilizes the compatibility of magnesium-aluminum spinels with high-valent platinum ions, and the mutual matching of the

[111] faces of platinum metal particles with the

[111] faces of magnesium-aluminum spinels. By adjusting the calcination atmosphere and temperature, highly dispersed platinum metal particles can be natively generated on the surface of the carrier to obtain a platinum-based catalyst with excellent anti-sintering performance. According to the literature (Actacrystallographica, 1976, A32: 751-767), magnesium ions Mg in the magnesium-aluminum spinel structure 2+ The radius is 0.086 nm, and the aluminum ion Al 3+ The radius is 0.053 nm, and the high oxidation state of platinum ions Pt 5+ The radius (0.071 nm) is smaller than that of magnesium ion Mg 2 + (0.086 nm), so the platinum ions can occupy the missing magnesium sites in the magnesium-aluminum spinel carrier lattice. The highly oxidized platinum ions located in the magnesium sites of the magnesium-aluminum spinel carrier lattice in the catalyst are very stable and need to be reduced at high temperature to obtain small-sized platinum metal nanoparticles natively on the surface. The amount of surface metallic platinum can be controlled by adjusting the temperature conditions of high-temperature reduction. The higher the reduction temperature, the more exposed metallic platinum nanoparticles.

[0017] 2. The present invention uses an alkali to precipitate Pt, Mg source and Al source together to form MgAl hydroxide containing precious metal Pt, and forms magnesium-aluminum spinel containing precious metal Pt by high-temperature (800 ℃~1000 ℃) air calcination. The radius of magnesium ions (0.086 nm) in the spinel structure is larger than that of high-oxidation state Pt ions (0.071 nm), so Pt can stably exist in the magnesium position of spinel in the form of high-oxidation state Pt ions, avoiding Pt sintering on the spinel surface to form large particles in a high-temperature air environment. There is lattice matching between the surface metallic platinum

[111] plane and the magnesium-aluminum spinel carrier structure

[111] plane, and the interaction of platinum ions inside the carrier makes the surface metallic platinum have the ability to resist high-temperature sintering.

[0018] 3. The present invention adopts high temperature (800℃~1000℃) reduction treatment to reduce part of the platinum ions originally in the magnesium position, and precipitate metal Pt nanoparticles on the surface, with a size range of 0.4-2.5nm. The number of precipitated nanoparticles is positively correlated with the reduction temperature, and the particle size remains unchanged. The

[111] crystal plane matching effect of spinel and the interaction with internal platinum ions jointly limit the further growth of surface Pt particles and improve the thermal stability of the catalyst. Even after aging treatment in propylene combustion reaction atmosphere at 1000℃ for 3 hours, the final catalyst still shows high activity in propylene combustion elimination reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 1 is a graph showing the relationship between the catalytic propylene combustion elimination efficiency and temperature before and after aging of the catalysts in Examples 1, 2 and 3.

[0020] Figure 2 This is a graph showing the relationship between the catalytic propylene combustion elimination efficiency and temperature before and after aging of the catalysts in Example 3 and Comparative Examples 1 and 2.

[0021] Figure 3 The carbon monoxide adsorption quantitative results and Pt dispersion of the catalysts of Examples 1, 2 and 3 are shown.

[0022] Figure 4 The X-ray diffraction spectra of the catalysts of Comparative Examples 1 and 2, and Examples 1, 4 and 5 are shown in FIG.

[0023] Figure 5 This is the X-ray photoelectron spectrum of Example 3 after different Ar purge etching treatment times.

[0024] Figure 6 This is a high-angle annular dark-field scanning transmission electron microscope photograph of Example 3. DETAILED DESCRIPTION

[0025] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment. Example 1

[0026] A sintering-resistant platinum-based catalyst is prepared by the following method: 1) Dissolve 0.009 mol magnesium acetate, 0.02 mol aluminum acetate and platinum nitrate in 250 mL deionized water (Pt concentration is 0.06 g / L).

[0027] 2) Prepare a NaOH solution with a concentration of 0.7 mol / L, add the NaOH solution to the mixed solution in 1), control the pH to 11-12, let it stand for 12 h, filter and wash the resulting precipitate, transfer it to an oven for drying, and grind it into powder.

[0028] 3) The powdered solid obtained in step 2) is calcined at 800° C. in air for 3 h to obtain a precursor in which platinum ions are located inside the crystal lattice.

[0029] 4) The precursor obtained in step 3) was calcined at 800 °C in a hydrogen atmosphere for 3 h to obtain PtMg 0.9 Al2O y -1, and the platinum content is 0.8 wt%. Example 2

[0030] A sintering-resistant platinum-based catalyst is prepared by the following method: 1) Dissolve 0.009 mol magnesium acetate, 0.02 mol aluminum acetate and platinum nitrate in 250 mL deionized water (Pt concentration is 0.06 g / L).

[0031] 2) Prepare a NaOH solution with a concentration of 0.7 mol / L, add the NaOH solution to the mixed solution in 1), control the pH to 11-12, let it stand for 12 h, filter and wash the resulting precipitate, transfer it to an oven for drying, and grind it into powder.

[0032] 3) The powdered solid was calcined at 800 °C in air for 3 h to obtain a precursor in which platinum ions were located inside the crystal lattice.

[0033] 4) The precursor was calcined at 900 °C in a hydrogen atmosphere for 3 h to obtain PtMg 0.9 Al2O y -2, with a platinum content of 0.8 wt%. Example 3

[0034] A sintering-resistant platinum-based catalyst is prepared by the following method: 1) Dissolve 0.009 mol magnesium acetate, 0.02 mol aluminum acetate and platinum nitrate in 250 mL deionized water (Pt concentration is 0.06 g / L).

[0035] 2) Prepare a NaOH solution with a concentration of 0.7 mol / L, add the NaOH solution to the mixed solution in 1), control the pH to 11-12, let it stand for 12 h, filter and wash the resulting precipitate, transfer it to an oven for drying, and grind it into powder.

[0036] 3) The powdered solid was calcined at 800 °C in air for 3 h to obtain a precursor in which platinum ions were located inside the crystal lattice.

[0037] 4) The precursor was calcined at 1000 °C in a hydrogen atmosphere for 3 h to obtain PtMg 0.9 Al2O y -3, platinum content is 0.8wt%. Example 4

[0038] Control the amount of platinum nitrate added to make the catalyst PtMg 0.9 Al2O y The platinum content is 0.1 wt %. The rest is the same as in Example 1. Example 5

[0039] Control the amount of platinum nitrate added to make the catalyst PtMg 0.9 Al2O y The platinum content is 4 wt %. The rest is the same as in Example 1.

[0040] Comparative Example 1 1) Impregnate a certain amount of platinum nitrate solution onto 1g of commercial alumina, put it into an oven to dry, and grind it into powder.

[0041] 2) The powdered solid was calcined at 800 °C in air for 3 h, and then switched to 800 °C in hydrogen atmosphere for 3 h to obtain Pt / Al2O3 with a platinum content of 0.8 wt%.

[0042] Comparative Example 2 A certain amount of platinum nitrate solution was impregnated into commercially available magnesium aluminum spinel, dried in an oven, ground into powder, calcined at 800 °C in air for 3 h, and then switched to 800 °C in hydrogen atmosphere for 3 h to obtain Pt / Mg1Al2O4 with a platinum content of 0.8 wt%.

[0043] The above examples and comparative examples were placed in a tube furnace and aged for 3 h in a flowing 0.2 vol.% C3H6 / 4 vol.% O2 atmosphere at 1000°C to obtain corresponding high-temperature aged samples (example-aged or comparative example-aged).

[0044] Catalyst performance test (1) The powder catalysts prepared from the examples and comparative examples and the high temperature aged samples were tableted and sieved to ensure that the particle size of the catalyst was between 40 and 60 meshes, and then the propylene catalytic combustion was evaluated in a fixed bed reactor. The evaluation conditions were: the total gas flow rate was 50 mL·min -1, gas composition is 0.2 vol.%C3H6 / 4 vol.%O2, N2 is used as the balance gas, and the mass space velocity is 30000 mL·g -1 ·h -1 .

[0045] The propylene concentration in the gas entering and leaving the fixed bed was detected by gas chromatography, and the propylene conversion rate was calculated.

[0046] The propylene conversion rate is calculated as follows:

[0047] Where: r C3H6 is the propylene conversion rate, [C3H6] inlet is the chromatographic area of ​​imported C3H6, [C3H6] inlet is the outlet C3H6 chromatographic area.

[0048] The reaction performance of the above catalysts for propylene combustion elimination is shown in Table 1 and Figure 1 and 2 shown.

[0049] Table 1

[0050] In Table 1, T 10 and T 90 They represent the corresponding temperatures when the propylene combustion conversion rate is 10% and 90%, respectively.

[0051] From Table 1 and Figure 1 and Figure 2 It can be seen that the T of the catalyst obtained in the embodiment of the present invention to propylene 10 Less than 150 ℃, T 90 Less than 250 ℃, while in Comparative Examples 1 and 2, their T 10 191 and 170 °C, respectively, T 90 The catalysts of Examples 1-5 and 258°C and 242°C, respectively, are much higher than those of the catalysts of Examples 1-5. This proves that the platinum-based catalyst prepared by the method of the present invention has high activity. Moreover, the present invention breaks the perception that conventional Pt catalysts are easily deactivated at high temperatures. The high-temperature reduction treatment of the catalyst of the present invention can improve the activity of PtMg1Al2O y The propylene combustion elimination activity of the catalyst can maintain good activity or stability when the reduction temperature is increased from 800°C to 1000°C. In addition, the activity of the catalysts of Examples 1, 2 and 3 decreases slightly after aging treatment. 10 and T 90 The temperature of Comparative Examples 1 and 2 increased by only about 10°C after aging. 10 and T 90All of them increased by 30-40 °C, among which Example 3 had the best activity, T 10 The temperature of the sample was reduced from 137°C in Example 1 to 117°C. 90 The activity of the comparative example is lower than that of the present invention, especially the typical example 3-aged catalyst, which further illustrates the excellent stability of the catalyst of the present invention. Compared with example 1, the amount of Pt added in examples 4-5 has changed. It can be seen that after aging, the activity of the catalyst has only slightly decreased, which shows that the Pt content of the catalyst of the present invention has a wide range of applications.

[0052] (2) Quantitative experiment of exposed Pt species on catalyst surface The quantification of exposed Pt species on the catalyst surface was obtained by carbon monoxide pulse adsorption experiments. The experiment was carried out on a Micromeritic Autochem II 2920 chemical adsorption instrument. 0.05 g of the catalyst was taken into a sample tube and reduced with 50 mL / min 10 vol.% H2 / N2 mixed gas at 300°C for 1 h. The gas was switched to He, purged for 0.5 h, and then cooled to room temperature. A pulse adsorption experiment was then carried out with 1 vol.% CO + 2 vol.% Ar + 97 vol.% He, and the adsorption signal of CO was detected by a Hiden VII mass spectrometer. Based on CO / Pt = 1, the amount of surface exposed Pt species can be calculated, and then the amount of surface exposed Pt species can be divided by the total Pt content of the catalyst to calculate the platinum dispersion.

[0053] The results are as follows Figure 3 As shown in the figure, it can be seen that the higher the reduction temperature, the higher the dispersion of Pt and the greater the adsorption of CO. This quantitative result proves that Examples 1, 2 and 3 have high platinum dispersions, among which the dispersion of Example 3 exceeds 70%, further illustrating the high thermal stability of the catalyst prepared by this method.

[0054] (3) X-ray photoelectron spectroscopy (XPS) test experiment of the catalyst after different Ar purge etching treatment times Ar purge etching treatment and XPS testing were both performed on a Thermo ESCALAB 250Xi instrument, and the intensity of Ar purge etching was set to the strong mode.

[0055] Figure 4 The X-ray diffraction spectra of the catalysts of Comparative Examples 1 and 2, Examples 1, 4 and 5 are shown in Table 1. Figure 4It can be seen that the catalysts of Comparative Examples 1 and 2 can both observe obvious diffraction peaks of metallic platinum, while only typical characteristic diffraction peaks of magnesium-aluminum spinel (PDF# 77-0435) are observed in Examples 1, 4 and 5. On the other hand, it is shown that the platinum-based catalyst prepared by the preparation method has good thermal stability and anti-sintering ability.

[0056] Figure 5 The X-ray photoelectron spectra of Example 3 after different Ar purge etching treatment times are shown in Figure 2. Figure 5 From the XPS spectra of different Ar etching treatment times, it can be seen that the signal of metallic Pt can be observed when not etched, and when the etching time reaches 500 s, the Pt species signal changes from a metallic state to an oxidized state, indicating that the distribution form of Pt in Example 3 is a surface metallic state, and exists in the form of oxidized ions inside. This distribution form ensures the excellent thermal stability of Pt on the catalyst.

[0057] Figure 6 This is a high-angle annular dark field scanning transmission electron microscope photo of Example 3. It can be seen that the particle size of the Pt nanoparticles on the catalyst surface is less than 2.5 nm, which proves the high dispersion of Pt in the example and that the surface Pt exists in the form of nanoparticles, not single atoms.

[0058] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents, without departing from the spirit and scope of the present invention. These changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A sintering-resistant platinum-based catalyst, characterized in that: The catalyst is a Pt-loaded magnesium-aluminum spinel structure catalyst, the total mass percentage of Pt in the catalyst is 0.1-4 wt%, the surface metal Pt exists in the form of nanoparticles with a size of 0.4-2.5 nm, and the magnesium-aluminum element ratio in the catalyst is 0.8-0.99:2; The catalyst is prepared by the following method: (1) Dissolve the corresponding salts of Pt source precursor, Mg source and Al source precursor in deionized water, wherein the Mg / Al molar ratio is 0.8:2~0.99:2, and then add excess alkali to control the pH to 11~12; (2) allowing the generated suspension to stand, filtering and washing the obtained precipitate, drying it, and grinding it into powder; (3) calcining the powdered solid at 800°C to 1000°C in air for 3 to 9 h to obtain a precursor in which platinum ions are located inside the crystal lattice; (4) The precursor obtained in step (3) is calcined at 800°C to 1000°C in a reducing atmosphere for 3 to 9 h to obtain the target catalyst PtMg x Al2O y ; The Pt component exists in the catalyst in two forms, one is in the form of metal nanoparticles on the surface of magnesium-aluminum spinel, and the other is in the form of high-valent cations located at the magnesium site in the magnesium-aluminum spinel lattice; the number of surface Pt metal nanoparticles is adjusted by adjusting the calcination temperature and calcination atmosphere of step (3) and step (4); the higher the reduction temperature, the greater the number of exposed metal Pt nanoparticles.

2. The sintering-resistant platinum-based catalyst according to claim 1, characterized in that: There is a Mg deficiency in the lattice of Mg-alumina spinel structure.

3. A method for preparing a sintering-resistant platinum-based catalyst as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Dissolve the corresponding salts of Pt source precursor, Mg source and Al source precursor in deionized water, then add excess alkali to control the pH to 11-12; (2) allowing the resulting suspension to stand, filtering and washing the resulting precipitate, drying it, and grinding it into powder; (3) calcining the powdered solid at 800°C to 1000°C in air for 3 to 9 h to obtain a precursor in which platinum ions are located inside the crystal lattice; (4) The precursor obtained in step (3) is calcined at 800°C to 1000°C in a reducing atmosphere for 3 to 9 h to obtain the target catalyst PtMg x Al2O y .

4. The method for preparing the sintering-resistant platinum-based catalyst according to claim 3, characterized in that: The Pt source precursor in step (1) includes platinum acetylacetonate, chloroplatinic acid, platinum nitrate or tetraammineplatinum nitrate.

5. The method for preparing the sintering-resistant platinum-based catalyst according to claim 3, characterized in that: The Mg source and Al source precursors in step (1) include corresponding sulfates, halides, nitrates or acetates.

6. The method for preparing a sintering-resistant platinum-based catalyst according to claim 3, characterized in that: The air conditions in step (3) include static and flowing states.

7. The method for preparing a sintering-resistant platinum-based catalyst according to claim 3, characterized in that: The reducing atmosphere in step (4) includes CO or H2 or a mixture of the two.

8. The method for preparing a sintering-resistant platinum-based catalyst according to claim 3, characterized in that: By adjusting the feed ratio of Mg source and Al source, the number of missing magnesium sites in the spinel structure lattice is controlled so that Pt is located at the missing magnesium sites. At the same time, by adjusting the calcination temperature and calcination atmosphere of step (3) and step (4), the number of surface Pt metal nanoparticles is adjusted. The higher the reduction temperature, the greater the number of exposed metal Pt nanoparticles.

9. Use of the sintering-resistant platinum-based catalyst according to any one of claims 1 to 2, characterized in that: The catalyst is used for catalytic combustion of propylene.

Citation Information

Patent Citations

  • Supported bimetal nanocrystal catalyst and preparation method thereof

    CN103157469A

  • Propane dehydrogenation catalyst and preparation method thereof

    CN108325523A

  • Sinter-resistant stable catalyst systems by trapping of mobile platinum group metal (PGM) catalyst species

    CN108355649A